РАЗВИТИЕ И СОВРЕМЕННОЕ СОСТОЯНИЕ ТЕОРИИ УПРАВЛЕНИЯ УСТОЙЧИВЫМ РАЗВИТИЕМ (Journal of Economic Research & Business Administration, 2015)
In the work presented in chronological sequence the initiation processes of sustainable development theory and its further development. Presents and analyzes definitions of sustainable development at different stages of its enhancement. Economic, social and environmental components of sustainable development theory are exposed. Also in this paper analyzes the current state of the theory of sustainable development. Definition of "sustainable economy" based on the distinction between different regulatory objectives, which lead to efficiency and equity are adduced. An analysis of the steady state economy (SSE), which adheres to environmental economists in the Francophone world and SSE, launched mainly in North America. Also in this paper were discussed strategic statements, including statements of Norwegian politics, which can make the transition from weak sustainable development (WSD) to a strong sustainable development (SSD).